Utilizing AI-based speech recognition technology in learning English pronounciation - Rama Dwika Herdiawan; marwah jaenudin, marwah jaenudin (Papanda Journal of English Education, 2023)
This research explores the potential of AI-based speech recognition technology to enhance English pronunciation learning. Through qualitative methods, including classroom observations and student interviews, the study investigates the impact of this technology on students' pronunciation accuracy, confidence, and overall learning experience. The findings demonstrate that AI-based speech recognition offers significant benefits, providing real-time feedback, personalized learning paths, and improved engagement, ultimately leading to more effective pronunciation acquisition. However, challenges such as the need for clear pronunciation and occasional misapplications by the technology were also identified. This research highlights the promise of AI in language learning and emphasizes the need for further development to optimize its effectiveness. Keywords: AI-based speech recognition, Technology in ELT, Pronunciation Learning